Mass participation and tournament event management for the team physician: a consensus statement (2022 update) - Herring, S. A.; Kibler, W. B.; Putukian, M.; Blauwet, C.; Boyajian-O'Neill, L. A.; Boyd, J.; Franks, R. R.; Indelicato, P. A.; Leclere L. E.; Logan, C.; O'Connar, F. G.; Matuszak, J.; et al. (Medicine & Science in Sports & Exercise, 2024)
Mass participation events include endurance events (e.g., marathon, triathlon) and/or competitive tournaments (e.g., baseball, tennis, football (soccer) tournaments). Event management requires medical administrative and participant care planning. Medical management provides safety advice and care at the event that accounts for large numbers of participants, anticipated injury and illness, variable environment, repeated games or matches, and mixed age groups of varying athletic ability. This document does not pertain to the care of the spectator.